Antidiabetic effect of Chrysophyllum albidum is mediated by enzyme inhibition and enhancement of glucose uptake via 3T3-L1 adipocytes and C2C12 myotubes - Benjamin Kingsley Harley (Asian Pacific Journal of Tropical Biomedicine, 2020)
Objective: To investigate the in vivo and in vitro antidiabetic potential of Chrysophyllum albidum. Methods: The effects of oral treatment with hydro-ethanolic extract (125, 250 and 500 mg/kg) of the stem bark of Chrysophyllum albidum and glibenclamide for 21 d on glucose level, serum enzyme markers for liver function, lipid profile, total protein, serum urea, serum creatinine, and body weight were evaluated in experimental diabetic rats administered with 45 mg/kg of streptozotocin. In vitro assays including glucose uptake in C2C12 cells and 3T3-L1 adipose tissues, α-glucosidase and α-amylase inhibition were employed to evaluate the possible mechanism of hypoglycemic action of the extract. DPPH and nitric oxide radical antioxidant activity of the extract was also measured. Results: The increased levels of blood glucose, triglycerides, low- density lipoprotein, total cholesterol, serum aspartate, and alanine transaminases, creatinine, and urea in the diabetic animals were reduced significantly (P<0.01) after treatment with Chrysophyllum albidum extract. The decreased total protein and high-density lipoprotein concentrations were normalized after treatment. In addition, the extract significantly (P<0.01) increased the transport of glucose in 3T3-L1 cells and C2C12 myotubes and exhibited considerable potential to inhibit α-amylase and α-glucosidase. It also demonstrated potent antioxidant action by scavenging considerably DPPH and nitric oxide radicals. Conclusions: Chrysophyllum albidum stem bark extract exhibits considerable antidiabetic effect by stimulating glucose uptake and utilization in C2C12 myotubes and 3T3-L1 adipocytes as well as inhibiting the activities of α-amylase and α-glucosidase.